2015
DOI: 10.1002/2015jd023786
|View full text |Cite
|
Sign up to set email alerts
|

Concentric gravity waves over northern China observed by an airglow imager network and satellites

Abstract: The first no-gap OH airglow all-sky imager network was established

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
87
0

Year Published

2016
2016
2018
2018

Publication Types

Select...
6

Relationship

4
2

Authors

Journals

citations
Cited by 65 publications
(101 citation statements)
references
References 42 publications
4
87
0
Order By: Relevance
“…Tropospheric convection is an important sources of atmospheric GWs [ Vadas and Fritts , ; Nakamura et al ., ; Snively and Pasko , ; Xu et al ., ]. Figure shows that the distributions of convective precipitations derived from ECMWF reanalysis data during the GWs are observed.…”
Section: Resultsmentioning
confidence: 96%
“…Tropospheric convection is an important sources of atmospheric GWs [ Vadas and Fritts , ; Nakamura et al ., ; Snively and Pasko , ; Xu et al ., ]. Figure shows that the distributions of convective precipitations derived from ECMWF reanalysis data during the GWs are observed.…”
Section: Resultsmentioning
confidence: 96%
“…The generated gravity waves can propagate upward and can modulate the airglow layers in the 80-100 km height range [Taylor and Hapgood, 1988;Taylor et al, 2007;Snively and Pasko, 2008]. Using the imaging nighttime airglow from ground observation sites [Taylor and Hapgood, 1988;Swenson and Mende, 1994;Chung et al, 2003;Sentman et al, 2003;Taylor et al, 2007;Suzuki et al, 2013;Xu et al, 2015] or spaceborne observation [Dewan et al, 1998;Mende et al, 1998;Yue et al, 2013;Akiya et al, 2014;Xu et al, 2015], gravity waves can be easily identified and observed. In addition, storm-generated gravity waves have also been confirmed by GPS data [Horinouchi and Tsuda, 2009;Lay et al, 2015].…”
Section: Introductionmentioning
confidence: 99%
“…The nonuniform distribution of wave sources around an observation station is an important factor to determine the anisotropy of the GWs propagation directions. Convective activity is an important source of high‐frequency GWs, which has been revealed from observations in the lower and middle latitudes (Li et al, ; Nakamura et al, ; Xu et al, ) and simulations (Alexander et al, , ; Vadas & Fritts, ; Walterscheid et al, ). Figure shows the distributions of convective precipitations derived from ECMWF reanalysis data.…”
Section: Resultsmentioning
confidence: 98%
“…The atmospheric circulation and structure in turn has important influences on local weather and global climates (McLandress et al, 2012). Convection, front/jet stream, orography, and wind shear in the troposphere are important sources of GWs (Eckermann & Vincent, 1993;Fritts, 1982Fritts, , 1984Li et al, 2016;Nakamura et al, 2003;Xu et al, 2015;Zhang, 2004). The auroral processes can also generate GWs (Oyama & Watkins, 2012).…”
Section: Introductionmentioning
confidence: 99%